Konsep Kedudukan Mahar dalam Perkawinan Islam Menurut Imam Syafi'i - Aulia, Mohamad Faisal; Fathir, Dwi (Pro Justicia: Jurnal Hukum dan Sosial, 2023)
This study aims to find out the concept of dowry position in Islamic marriage according to Imam Shafi'i. This type of research is library research, which is research that seeks to obtain data using library sources. The results of this study show that in Islamic marriages pay dowry to them as a sincere gift. The gift is a dowry, the size of which is determined by the agreement of both parties, since the gift must be done sincerely. The position of dowry according to Imam Shafi'I, namely Dowry is a mandatory gift given by a husband when his wife is in exchange for intercourse. The position of dowry is not a pillar in marriage but as a condition for the validity of marriage. The postulate used by Imam Shafi'i is the Qur'an surah Al-Baqarah 236. The law in the verse indicates that it is not obligatory to give dowry to the wife if the husband divorced her before dukhul and has not determined the dowry. This means that if the wife has been interfered with, she must determine the dowry.